Phytolacca acinosa Roxb. (Phytolaccaceae), a new alien species in the Croatian flora - Borak Martan, Valentina; Sostaric, Renata (Acta Botanica Croatica, 2016)
Phytolacca acinosa Roxb., an East Asian plant species naturalised in many parts of the European continent, has been recorded for the first time in Croatia in two anthropogenic habitats in Varaždin city (NW Croatia). This study reports the newly discovered localities and presents the characteristics of the new alien species in the flora of Croatia. A determination key is given for Phytolacca taxa registered in Croatia and neighbouring countries.